Connexins and microRNAs: Interlinked players in regulating islet function?. Issue 5 (3rd September 2017) - Umrani, Malati R.; Joglekar, Mugdha V.; Somerville Glover, Ella; Wong, Wilson; Hardikar, Anandwardhan A.
ABSTRACT: Pancreatic β-cells are connected to neighboring endocrine cells through the adherin proteins and gap junctions. Connexin 36 (Cx36) is one of the most well-studied and abundantly expressed gap-junction proteins within rodent islets, which is important in coordinated insulin secretion. The expression of connexins is regulated at various levels and by several mechanisms; one of which is via microRNAs. In past 2 decades, microRNAs (miRNAs) have emerged as key molecules in developmental, physiologic and pathological processes. However, very few studies have demonstrated miRNA-mediated regulation of connexins. Even though there are no reports yet on miRNAs and Cx36; we envisage that considering the important role of connexins and microRNAs in insulin secretion, there would be common pathways interlinking these biomolecules. Here, we discuss the current literature on connexins and miRNAs specifically with reference to islet function.